Cost-effectiveness analysis of first-line pembrolizumab treatment for PD-L1 positive, non-small cell lung cancer in China. (3rd April 2019) - Liao, Weiting; Huang, Jiaxing; Hutton, David; Li, Qiu
Abstract: Purpose: Pembrolizumab was recently approved in several countries as a first-line treatment for patients with PD-L1 positive, non-small cell lung cancer (NSCLC). However, it is expensive. This study aimed to assess the cost-effectiveness of pembrolizumab in treating advanced NSCLC patients with PD-L1 positive cancer in China. Methods: A Markov model was developed to compare the cost-effectiveness of pembrolizumab with chemotherapy for patients with PD-L1 expression on at least 50% of NSCLC tumor cells. Model inputs for transition probabilities and toxicity were derived from published clinical trial data, while health utilities were estimated from a literature review. Costs for drugs were updated to standard fee data from West China Hospital in 2017. Health outcomes were measured in quality-adjusted life years (QALYs), and cost-effectiveness was measured as the incremental cost-effectiveness ratio (ICER). Sensitivity analyses were conducted to test the robustness of the model. Results: Pembrolizumab gained 0.45 QALYs at an incremental cost of 46, 362 compared to chemotherapy for an ICER of 103, 128 per QALY gained. In most scenarios, the ICER exceeded three times the Chinese Gross Domestic Product per capita. Two-way sensitivity analysis showed that, when the utility of the progression-free status increased to the maximal value of 0.845 and the 1 mg dose price decreased to 10.50, the ICER reduced to 25, 216/QALY. Conclusions: Pembrolizumab is not likely to be cost-effective in the treatment of PD-L1 positive, NSCLC for Chinese patients. Less aggressive pricing may increase accessibility for patients in China.